DINAMIKA PEMIKIRAN KLASIFIKASI ILMU DALAM KHAZANAH INTELEKTUAL ISLAM KLASIK - Muhammad Zainal Abidin (Jurnal Ilmiah Ilmu Ushuluddin, 2021)
The idea of science integration which is an important issue of Muslims today demands attention to the study of science classification. This topic is among the least touched in discussions related to Islam and science. This article is the result of a literature review that raises classical Muslim intellectual thoughts related to the classification of science. During the heyday of Islam, this issue received serious attention from many Muslim intellectuals at that time. The important findings from this paper are that: First, the repertoire of thought in the classification of science in Islam shows the great enthusiasm of Muslim scientists in the development of science whose impact can be felt today. Second, although there are various variations in the classification of science, they still provide respect and space for metaphysical or religious sciences. Third, there are two patterns in the classification of science as stated by Muslim scientists, some are strongly influenced by the Greek tradition, and some are based on Islamic treasures. This division in the present context, this idea is similar to the view of Islamization of science and the view of Islamic scholarship.